Developable Surface Patches Bounded by NURBS Curves (Journal of Computational Mathematics, 2020)
In this paper we construct developable surface patches which are bounded by tworational or NURBS curves, though the resulting patch is not a rational or NURBS surfacein general. This is accomplished by reparameterizing one of the boundary curves. Thereparameterization function is the solution of an algebraic equation. For the relevant caseof cubic or cubic spline curves, this equation is quartic at most, quadratic if the curves areBézier or splines and lie on parallel planes, and hence it may be solved either by standardanalytical or numerical methods.